2016
DOI: 10.1080/10410236.2016.1177898
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effects of Family Communication Patterns on the Decision to Disclose a Health Issue to a Parent: The Benefits of Conversation and Dangers of Conformity

Abstract: Family can be a key site of support for individuals who are diagnosed with a health issue, as long as the health condition is known within the family unit. This online experiment investigated variables that influence the likelihood that college students will disclose a hypothetical health issue to a parent. Family communication patterns (FCP) theory informed this analysis by outlining the role of FCP in disclosure dynamics among college students and their parents. Through structural equation modeling, a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Disclosing an STI to a parent is a difficult process, potentially requiring a great deal of efficacy. Families high in conversation talk about a variety of topics and allow members to express their concerns, so it is likely that individuals in this type of family also talk about health issues and behaviors, that is, the efficacy to communicate personal information such as an STI status may be a hallmark of individuals from conversation-oriented families, especially as EAs from high conversation families are more likely to disclose health issues to parents [ 43 ], partially due to increased communication efficacy [ 44 ], a consistently strong indicator of health self-disclosure [ 45 ]. On the other hand, EAs from more conformity-oriented families may feel less able to disclose their STI status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disclosing an STI to a parent is a difficult process, potentially requiring a great deal of efficacy. Families high in conversation talk about a variety of topics and allow members to express their concerns, so it is likely that individuals in this type of family also talk about health issues and behaviors, that is, the efficacy to communicate personal information such as an STI status may be a hallmark of individuals from conversation-oriented families, especially as EAs from high conversation families are more likely to disclose health issues to parents [ 43 ], partially due to increased communication efficacy [ 44 ], a consistently strong indicator of health self-disclosure [ 45 ]. On the other hand, EAs from more conformity-oriented families may feel less able to disclose their STI status.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this same study, young adults in high‐conformity families were more likely to report lower healthy attitudes and receive less confirmation of health‐specific conversations. Additionally, children from high‐conformity families are also more likely to keep secrets from parents about health‐related issues (Hays, Maliski, & Warner, ). Although not an FCP study, Ichiyama et al's () work is relevant to our current discussion.…”
Section: Family Communication Patterns Theorymentioning
confidence: 99%
“…An additional challenge in protective families is that they report the strongest traitlike orientations to privacy (Bridge & Schrodt, 2013). Children are more likely to keep secrets from parents about health-related issues (Hays et al, 2017). Ultimately, inoculation messages that promote family norms around explicit rules and privacy between parents and children (Bridge & Schrodt, 2013) might bypass psychological reactance (Brehm & Brehm, 1981) that stems from privacy violations.…”
Section: Protective Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Families with high conversation orientation encourage open and equal communication and downplay the homogeneity of values and attitudes among family members, and vice versa. Previous studies found that conversation orientation was positively related to parent–child communication satisfaction, and predicted family members’ positive health attitudes and behaviors, such as sensitive health issue disclosures, mental health, and physical training [ 41 , 42 ]. Conversely, conformity orientation is usually linked to negative communication outcomes, including communication dissatisfaction, children’s stress, and concealment of health issues [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%